72.6k views
2 votes
Find h'(-4) if
h=(f\circ g), , f(x) = −6x² + 7 and the equation of the tangent line of g at -4 is y = 10x - 8

1 Answer

6 votes

Answer:


h'(-4) = 5760

Explanation:

We are given the function:


\displaystyle h(x) = (f\circ g)(x)

And we want to find h'(-4) given:


\displaystyle f(x) = -6x^2 + 7

And that the equation of the tangent line of g at x = -4 is y = 10x - 8.

Recall that (f ∘ g)(x) = f(g(x)). Hence:


\displaystyle h(x) = f(g(x))

Find h'(x). We can take the derivative of both sides with respect to x:


\displaystyle (d)/(dx)\left[ h(x)\right] = (d)/(dx)\left[ f(g(x))\right]

By the chain rule:


\displaystyle h'(x) = f'(g(x)) \cdot g'(x)

Therefore:


\displaystyle h'(-4) = f'(g(-4)) \cdot g'(-4)

A) Finding f'(g(-4)):

Recall that we are given that the equation of the tangent line of g at x = -4 is:


\displaystyle y = 10x - 8

Since this is tangent, it tells us that at x = -4, line y touches g. Therefore, y(-4) = g(-4). Find y(-4):


\displaystyle \begin{aligned} y(-4)&= 10(-4) - 8 \\ \\ &= -48\end{aligned}

Hence, g(-4) = -48. Consequently, f'(g(-4)) = f'(-48).

Find f'(x):


\displaystyle \begin{aligned} f'(x) &= (d)/(dx)\left[ -6x^2 + 7\right] \\ \\ &= -12x\end{aligned}

So:


\displaystyle \begin{aligned} f'(-48) &= -12(-48) \\ \\ &= 576\end{aligned}

Therefore, f'(g(-4)) = 576.

B) Finding g'(-4):

Recall that by definition, the derivative of a function at a point is the slope of the tangent line to the point.

The tangent line to g at x = -4 is given by:


y = 10 x- 8

The slope of the line is 10. Therefore:


g'(-4) = 10

Hence:


\displaystyle \begin{aligned}h'(-4) &= f'(g(-4)) \cdot g'(-4) \\ \\ &= (576) \cdot (10) \\ \\ &= 5760 \end{aligned}

In conclusion:


h'(-4) = 5760

User Dansalias
by
6.1k points